Quantification of sexual behaviour traits in presence of teaser male in relation to libido and semen quality in crossbred (HF x Sahiwal) bulls - SINGH, KHUSHPREET; KUMAR, AJEET; HONPARKHE, M; BRAR, P S (The Indian Journal of Animal Sciences, 2020)
The present study was conducted to quantify the sexual behaviour traits of crossbred (HF x Sahiwal) bulls in presence of male teaser in relation to libido and semen quality. The average duration of first licking of perineal area, average frequency and overall average duration of licking of perineal area until ejaculation in high libido bulls were significantly (P